2014
DOI: 10.1186/1757-7241-22-28
|View full text |Cite
|
Sign up to set email alerts
|

The impact of severe traumatic brain injury on a novel base deficit- based classification of hypovolemic shock

Abstract: BackgroundRecently, our group has proposed a new classification of hypovolemic shock based on the physiological shock marker base deficit (BD). The classification consists of four groups of worsening BD and correlates with the extent of hypovolemic shock in severely injured patients. The aim of this study was to test the applicability of our recently proposed classification of hypovolemic shock in the context of severe traumatic brain injury (TBI).MethodsBetween 2002 and 2011, patients ≥16 years in age with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Four studies [7,26,27,38] had selected a sample of patients reflecting a valid estimate (external validity in regard to our question). Twelve studies [7,17,26,32,33,37,39,[41][42][43][44][45] reported information on the way they collected transfusion data that were concordant with a low risk of measurement error. Fifteen studies [7,[26][27][28]32,33,[36][37][38][41][42][43]45,47,48] collected data on RBC transfusion during ICU stay or full hospitalization.…”
Section: Risk Of Bias Within and Across Studiesmentioning
confidence: 91%
See 4 more Smart Citations
“…Four studies [7,26,27,38] had selected a sample of patients reflecting a valid estimate (external validity in regard to our question). Twelve studies [7,17,26,32,33,37,39,[41][42][43][44][45] reported information on the way they collected transfusion data that were concordant with a low risk of measurement error. Fifteen studies [7,[26][27][28]32,33,[36][37][38][41][42][43]45,47,48] collected data on RBC transfusion during ICU stay or full hospitalization.…”
Section: Risk Of Bias Within and Across Studiesmentioning
confidence: 91%
“…Fifteen studies [7,[26][27][28]32,33,[36][37][38][41][42][43]45,47,48] collected data on RBC transfusion during ICU stay or full hospitalization. Eighteen studies [7,17,[28][29][30][31][32][33][34][35][36][37][38][39]41,45,47,49] reported a proportion of missing data less than 10%.…”
Section: Risk Of Bias Within and Across Studiesmentioning
confidence: 96%
See 3 more Smart Citations